Siamese White - Collis, Maurice, (Brill | Manohar Publishers & Distributors, 2024)
The book is about the career of Samuel White during his stay in the Siam region, which is the modern-day Thailand. White was declared the ruler of Siam under James II of England. The book contains a description of the Anglo-Siamese War, which was conducted in the year 1687-88, which was between the English East India Company and the Kingdom of Siam. The book also contains a letter from White related to his kinsmen, preserved in the Bath Municipal Library, which dates back to 1683.